Kinetics of arylation of 3-bromo-benzophenone with n-butylacrylate using NC palladacycle catalyst - Atla, Shashi B.; Rajurkar, Kalpendra B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
The kinetics of arylation of n-butylacrylate (n-BA) with 3-bromo-benzophenone (BBP) using a monomeric palladacycle complex [Pd(ppy)(PPh(3))(OTs)](ppy=2-phenylpyridine) catalyst has been studied. The effect of concentration of the substrate, base (NaOAc), and catalyst was studied at three different temperatures (413-433 K). The rate was found to be first order with respect to catalyst, first order tending to zero order with respect to n-butylacrylate and NaOAc concentrations. The rate passed through a maximum with variation of BBP concentration. The observed results have been explained on the basis of formation of Pd species (PdX(2), PdX(3)(-), PdX(4)(2-), and Pd(2)X(6)(2-)) which are inactive for the Heck reaction. Various empirical rate equations were considered to fit the rate data and the best fitting model has been selected. The rates predicted by model were found to be in good agreement with the observed experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arylation; Heck reaction; kinetics; Palladacycle

Kinetics of hydroformylation of camphene using rhodium-phosphite catalyst - Pagar, Nitin S.; Rajurkar, Kalpendra B.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2020)
Kinetics of hydroformylation of camphene was investigated in the presence of [Rh(CO)(2)(acac)]/P(OPh)(3) catalyst in a temperature range of 363-383 K. The influence of parameters such as stirring speed, camphene, catalyst, ligand concentrations, and partial pressures of H-2 and CO on the activity and selectivity of the catalyst has been studied. The rate showed a first-order dependence with respect to catalyst and camphene concentrations. The effect of partial pressure of hydrogen showed fractional order dependence. The plots of rate versus excess ligand, that is, (P(OPh)(3)) concentration and rate versus CO partial pressure passed through maxima and showed typical substrate/ligand inhibited kinetics. An empirical rate equation has been proposed and found to be in good agreement with the observed rate data. The kinetic parameters and activation energy were also evaluated.
Keywords: camphene; homogeneous; Hydroformylation; kinetics; rhodium-phosphite

Kinetic investigation on palladium-catalyzed carbonylation of allyl alcohol - Tonde, Sunil S.; Rajurkar, Kalpendra B.; Pagar, Nitin S. (International Journal of Chemical Kinetics, 2025)
Palladium-catalyzed carbonylation of allyl alcohol to 3-butenoic acid has been investigated. A significant effect of halide promoters, p-tolylsulfonic acid (TsOH), water, solvents, and PPh3 concentration activity and selectivity has been studied. Detailed kinetics of this reaction was investigated in a temperature range of 363-383 K. The influence of parameters such as stirring speed, allyl alcohol, catalyst, benzyltriethylammonium chloride (BTEAC), TsOH concentrations, and CO partial pressures on the activity and selectivity has been studied. An empirical rate equation was suggested and found to be fairly consistent with observed rate data. In addition, the activation energy and kinetic parameters were evaluated.
Keywords: allyl alcohol; Carbonylation; halide promoters; kinetics; Mechanism; Palladium

Kinetics of palladium catalyzed methoxycarbonylation of vinyl acetate to methyl-2-acetoxypropionate for the synthesis of lactic acid - Tonde, Sunil S.; Rajurkar, Kalpendra B.; Pagar, Nitin S. (International Journal of Chemical Kinetics, 2026)
Lactic acid is crucial for food production and energy generation in body. It also has been a key monomer of poly lactic acid, biodegradable plastic. As methoxy carbonylation of vinyl acetate (VAM) produces methyl-2-acetoxypropionate, and methyl lactate as intermediates for lactic acid, its kinetic investigations are important to understand the reaction behavior. In this paper a study was conducted on the kinetics of methoxyarbonylation for vinyl acetate in a semi-batch slurry reactor across a temperature range of 363-383K, utilizing [PdCl2(PPh3)2] catalyst. The effect of catalyst, methanol, vinyl acetate monomer (VAM) concentration and partial pressure of carbon monoxide (CO) on the reactants and products concentration was investigated with respect to time. Catalytic methoxycarbonylation of VAM produces methyl acetoxy propionate which further forms methyl lactate and methyl acetate through consecutive reaction. Methyl acetoxy propionate and methyl lactate thus formed can be converted to lactic acid through hydrolysis. The methoxycarbonylation conditions produce byproducts dimethyl acetate and methyl acetate through parallel reaction. Based on the initial rate data of formations of lactic acid precursors through methoxycarbonylation and consecutive reaction byproducts through parallel reaction, and trend behavior of initial rates with concentrations of reactants, different empirical rate equations were evaluated. The integral concentration-time data was fitted to evaluate the kinetic parameters at various temperatures. General elimination method and thermodynamic principles were used to suggest an appropriate empirical rate equation as shown below.r1, r2, and r3 are rates of methoxycarbonylation reaction (methyl-2-acetoxypropionate formation), consecutive reaction (methyl lactate formation) and parallel reaction (dimethyl acetal formation) respectively. k1, k2, and k3 are equilibrium constants for the reactions r1, r2, and r3 respectively. KB and KC are equilibrium constants for VAM and methanol CA, CB, CC, CD and CW are concentration of dissolved CO in the liquid phase, VAM, methanol, methyl-2-acetoxypropionate and catalyst respectively. For catalyst and CO, the methoxycarbonylation reaction rate was observed to be first order, while for VAM and methanol, it was first order with a tendency to zero order. Energy of activation needed for the catalytic reaction was 81.62 kJ/mol. For a catalytic reaction, selectivity towards the required product is desirable. Kinetic investigations can be utilized to achieve maximum selectivity towards the desired products at optimum reaction rate. The proposed model suggests that 95%-97% selectivity towards the combined carbonylated products (methyl-2-acetoxypropionate and methyl lactate) can be achieved.
Keywords: Hydrolysis; kinetics; Lactic acid; Methoxycarbonylation; methyl lactate; methyl-2-acetoxypropionate; palladium catalyst; VAM